2010
DOI: 10.1111/j.1744-7976.2010.01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Benefits of Controlling Forest Insect Outbreaks: A Contingent Valuation Analysis in Two Canadian Provinces

Abstract: This study estimates the social benefits of controlling two very different forest insect outbreaks in New Brunswick (NB) and Saskatchewan (SK), namely spruce budworm (SBW) (Choristoneura fumiferana) and forest tent caterpillar (FTC) (Malacosoma disstria). Using dichotomous choice contingent valuation mail surveys, households in NB and SK were asked to indicate their willingness‐to‐pay (WTP) for controlling future SBW and FTC outbreaks. A majority of respondents (over 80% in each province) favored controlling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For example, Walsh et al's (1990) study finds substantial nonuse values for the protection of ponderosa pines in Colorado from native, mountain pine beetle outbreaks (with only $14 of the average annual total value of $52 for 150 trees per acre allocated to recreation-use), and Loomis et al (1996) find significant WTP ($90 per household per year) to reduce fire hazards to Pacific Northwestern old-growth forests, again with the CV method. Highlighting the importance of the context of management, Chang et al (2011) find substantially different WTP to control future outbreaks of two different native forest pests, spruce budworms and forest tent caterpillars, in the Canadian provinces of New Brunswick and Saskatchewan, with point estimates of mean WTP ranging between $33 and $104 per household per year.…”
Section: Nonmarket Benefits Of Forest Invasive Species Managementmentioning
confidence: 99%
“…For example, Walsh et al's (1990) study finds substantial nonuse values for the protection of ponderosa pines in Colorado from native, mountain pine beetle outbreaks (with only $14 of the average annual total value of $52 for 150 trees per acre allocated to recreation-use), and Loomis et al (1996) find significant WTP ($90 per household per year) to reduce fire hazards to Pacific Northwestern old-growth forests, again with the CV method. Highlighting the importance of the context of management, Chang et al (2011) find substantially different WTP to control future outbreaks of two different native forest pests, spruce budworms and forest tent caterpillars, in the Canadian provinces of New Brunswick and Saskatchewan, with point estimates of mean WTP ranging between $33 and $104 per household per year.…”
Section: Nonmarket Benefits Of Forest Invasive Species Managementmentioning
confidence: 99%
“…Better estimates might change the cost-effectiveness and efficiency ranking of forest protection strategies. Further, the non-market benefit estimates in this study, from Chang et al [20], only included recreation and wildlife values. These values may have changed over time, and other non-market values such as carbon and water quality, which were not valued, may be important to the NB population.…”
Section: Discussionmentioning
confidence: 99%
“…Non-market benefits of each SBW control effort were adopted from the Chang et al [20] willingness to pay (WTP) estimation of the public's benefit from controlling future SBW outbreaks in NB. A contingent valuation method (CVM) analysis determined that average WTP was $86.19 (CAD 2007) per household per year for 5 years (2007-2011), including timber value, which was considered a market benefit, or $53.87 for the non-market benefit [20]. The associated value for a moderate SBW outbreak was estimated in proportion to the volume lost.…”
Section: Benefit-cost Analysismentioning
confidence: 99%
“…The results of their survey suggested that social benefits can be large, ranging between CAD$14.3–32.4 million per year for SBW and CAD$7.9–22.0 million for FTC. This study, along with an advanced SBW DSS model (Hennigar et al 2013), was then used by Chang et al (2012a) to conduct another CBA of controlling SBW in New Brunswick. The CBA evaluated six scenarios, which included three proposed protection levels and two unprotected outbreak severities.…”
Section: Introductionmentioning
confidence: 99%
“…In a unique non-market valuation study, Chang et al (2011) used contingent valuation to estimate the social benefits of SBW and FTC control also in Saskatchewan and New Brunswick. The results of their survey suggested that social benefits can be large, ranging between CAD$14.3-32.4 million per year for SBW and CAD$7.9-22.0 million for FTC.…”
Section: Canadian Applications Of Economic Analysis To Forest Insect mentioning
confidence: 99%